Permasalahan-Permasalahan Sekolah Menengah Pertama (Smp) Bunda Dalam Pembelajaran Jarak Jauh Sebagai Dampak Pandemi Covid-19 - Syairul Bahar (STIT Muslim Asia Afrika, 2020)
Corona virus disease 2019 or Covid-19 is a virus that is very dangerous in human life, it can affect all aspects, especially education. This case made the Minister of Education and Culture took a decision in order to prevent and break the chain of spread of the covid-19 virus, that is implementing online learning in every school start from elementary schools to universities. This research uses an exploratory case study method and the research approach uses a qualitative case study method which is used to obtain information on online learning problems as a result of the Covid-19 pandemic on teaching and learning activities at SMP Bunda. Based on the results of the interview, the problems in online learning that were experienced by the teachers are wasteful use of quotas or internet credit, trouble of signals or internet networks, the material presented has not been able to build interactions between students and teachers, the expected results are not more optimal, and it is difficult to motivate student to study, the result there is lack of awareness of students in completing the tasks. In addition, the problems in online learning that were experienced are first, the tasks that were given by the teachers are very many with relatively short assignments submit, so that students have an impact on lack of sleep time and feeling stress. Second, connection or Internet networks also often became problematic for them, and the last, Teacher sometime explains the material quickly and the results are many students have difficulty to catch the material. Therefore, it is necessary for the cooperation all the subject to solve problems that arise as a result of online learning.